2015
DOI: 10.1108/ijhcqa-02-2014-0017
|View full text |Cite
|
Sign up to set email alerts
|

The trust-commitment challenge in service quality-loyalty relationships

Abstract: This study explores using the SQAS scale in a private healthcare context. The authors provide further evidence that service quality is an antecedent and different from satisfaction. All the measures used proved to be valid and reliable. Trust and commitment play different roles in their relationship with loyalty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
99
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 32 publications
14
99
0
7
Order By: Relevance
“…The purpose of the current study was to investigate the predict power of relationship quality, patient gratitude, and alternative attractiveness on patient loyalty. The results of our study revealed that satisfaction and commitment were found to contribute to patient loyalty, which are consistent with previous studies that indicated that a solid loyalty could be stimulated by patients' perceived satisfaction in the hospital services and also by a supportive commitment from the hospital in the healthcare service industry [30], [31]. However, trust does not have a significant effect on patient loyalty.…”
Section: Discussionsupporting
confidence: 82%
“…The purpose of the current study was to investigate the predict power of relationship quality, patient gratitude, and alternative attractiveness on patient loyalty. The results of our study revealed that satisfaction and commitment were found to contribute to patient loyalty, which are consistent with previous studies that indicated that a solid loyalty could be stimulated by patients' perceived satisfaction in the hospital services and also by a supportive commitment from the hospital in the healthcare service industry [30], [31]. However, trust does not have a significant effect on patient loyalty.…”
Section: Discussionsupporting
confidence: 82%
“…It was also found that trust holds a significant relationship with commitment in various service-related contexts as well as in a luxury brand context (Moreira and Silva, 2015;Ou et al, 2011;Sumaedi, Juniarti and Bakti, 2015;Shukla et al, 2016). Therefore, the two relationship quality factors, trust and commitment, are hypothesised to have significant relationships with each other while trust also has a significant relationship with the behavioural intention of customers in relation to postpurchase service and repairs at a luxury motor vehicle dealership.…”
Section: The Relationships Between Trust Commitment and Behavioural mentioning
confidence: 95%
“…Commitment has also been found to be significantly related to behaviour intention and, with respect to its different categories as proposed by Parasuraman et al (1994), to different service, retail and luxury brand contexts (Fullerton, 2014;Jani and Han, 2011;Liang and Wang, 2007;Moreira and Silva, 2015;Shukla, Banerjee and Singh, 2016). Therefore, two relationship quality factors -customer satisfaction and commitment -are hypothesised to have significant relationships with each other and the behavioural intention of customers when post-purchase service and repairs at a luxury motor vehicle dealership are considered.…”
Section: The Relationships Between Customer Satisfaction Commitment mentioning
confidence: 96%
“…The interaction and result qualities impact positively to the patient's trust in the hospital, but has no significant effect to the environmental quality. Developing trust leads to a positive attitude and loyalty from the patients (Moreira & Silva, 2015). Trust acts as an intermediate in the relationship between satisfaction with service recovery, cumulative satisfaction and relationship between positive emotions and loyalty.…”
Section: H2: Corporate Social Responsibility Impacts To the Customer mentioning
confidence: 99%